EFFECT OF INQUIRY TRAINING LEARNING MODEL DAN CREATIVITY ON SCIENCE PROCESS SKILLS - Purnama Silitonga; Mara Bangun Harahap; Derlina . (Universitas Negeri Medan, 2016)
This study aims: 1) to determine differences in science process skills of students with learning model inquiry training and conventional learning models, 2) to determine the difference science process skills of students who have high creativity and creativity is low, 3) to determine the interaction model of learning inquiry trainingwith creativity of the science process skills. The sampling technique conducted cluster random sampling two classes, where first class as a class experiment with the number of students 32 people applied learning model inquiry training (X-1) and the second class as a class control the number of students 32 people who applied conventional learning model ( X-2). Instruments in this study is the science process skills test and a test of creativity in the form of a description. From these results it can be concluded that: 1) science process skills of students that learned with a learning model inquiry training is better than the students that learned with conventional learning models, 2)science process skills of students with high creativity better than students with creativity is low, 3) there is interaction between inquirylearning model training and creativity in influencing the science process skills of students.